Treatment of Locally Advanced Prostate Cancer: A Case Report and Narrative Review - Frank Peinemann; Michael Pinkawa (Case Reports in Urology)
Introduction. Treatment of locally advanced prostate cancer is under discussion. Differences between clinical and pathological staging and risk factors such as positive surgical margins and seminal vesicle involvement challenge the individual treatment decisions. Case Presentation. Clinical tumor stage before treatment was assessed to be T2. After radical prostatectomy, pathological examination revealed the stage pT3b N0 M0 including positive surgical margin and seminal vesicle involvement. Early adjuvant androgen deprivation therapy and late adjuvant radiation therapy were added in response to the pathological risk factors. No evidence of disease was observed for 15 years after the treatment. The unexpected pathological findings were not explained by the physicians in charge. Discussion. A narrative review of the recent literature showed that multiple treatment modalities including adjuvant radiotherapy following radical prostatectomy are consistent with current recommendations. The multimodal approach has possibly cured a high-risk patient and may also work successfully in other patients. An alternative treatment option with better preservation of health-related quality of life might have also achieved a similar good overall survival.